ANALYZING THE INFLUENCE OF RETURN ON ASSET, DEBT-TO-EQUITY RATIO, AND NET PROFIT MARGIN TOWARD STOCK RETURN ON TELECOMMUNICATION COMPANY (EVIDENCE FROM COMPANIES LISTED IN BEI 2010-2019) - Hosea, Sheila S.; Kindangen, Paulus; Worang, Frederik G. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: Nowadays, telecommunication sector plays an important role in development of any economy. As technology develops rapidly, making the telecommunications sector more advanced, so that many investors have begun to be interested in investing their funds on telecommunication companies. Stock return is the level of profit to be gained by investors who invest their funds in the capital market in the form of realization return and expected return. The aim of this paper is to measure financial performance of the Indonesian Telecommunication Company during the years 2010-2019. This paper analyzed the influence of independent variables which include Return on Assets, Debt to Equity Ratio, and Net Profit Margin toward Stock Return. This study uses secondary data derived from annual financial reports from 5 telecommunications companies in the infrastructure, utilities and transportation sector listed on the Indonesia Stock Exchange. The sample collection has been carried out by using purposive sampling method. The data analysis technique has been done by using multiple linear regression test. Based on the result of the analysis, it can be concluded that (1) Return on Assets have significant and positive influence on stock return, (2) Debt to Equity Ratio and Net Profit Margin have no significant influence on stock return in Telecommunication companies.Â Keywords: Return on Assets, Debt to Equity Ratio, Net Profit Margin, Stock Return, telecommunication